A Longitudinal Study on Covid-19 Confinement and Impact on Physical Activity of Medical Students of Rawalpindi - Mashhadi, Syed Fawad; Rasool, Faizan; Malick, Sohaib Abdul; Ishtiaq, Mehroze; Mukhtar, Muhammad Omar; Ayub, Tahira; Shahid, Maheen (Pakistan Armed Forces Medical Journal, 2024)
Objectives: The objectives of the study were to assess the impact of COVID-19 confinement on different aspects of physical activity and sedentary time of medical students with special emphasis on gender. Study Design: This was a longitudinal study in which two samples were taken, one during the confinement period and one after it, to assess the differences between the time spent on physical activity and sedentary time. Place and During of Study: This study was conducted on a total of 300 medical students from two medical colleges of Rawalpindi. The study extended from Apr till Jun 2021 over a period of two months. Methodology: Modified International Physical Activity Questionnaire (IPAQ) was used as a data collection tool. The respondents filled the questionnaire twice. First during COVID-19 confinement and the second, after the confinement ended. Results: A total of 300 individuals were selected to fill in the questionnaire, 200 of them filled in the first questionnaire. The second questionnaire was, however, filled by only 146 individuals and the rest were lost to follow-up.The 146 participants in our study were all students in medical schools in Rawalpindi/Islamabad Pakistan. Out of the total 43.2%(63) were male, while 56.8%(83) were female. The mean age was 20.18±1.72. Post confinement, the amount of time spent on moderate and vigorous activities by all the individuals increased by 26.7% and 82.5%, respectively. In addition, walking time was increased by 82%, sedentary time was also reduced by 36.4%. Conclusion: Physical activity of both men and women was found to be reduced during COVID-19 confinement along with increased sedentary time as compared to their normal routine.